CqPP2A inhibits white spot syndrome virus infection by up-regulating antimicrobial substances expression in red claw crayfish Cherax quadricarinatus. (March 2021) - Gao, Rui-lin; Liu, Ling-ke; Guo, Li-mei; Wang, Ke-jian; Liu, Hai-peng
Abstract: Protein phosphatase 2A (PP2A) is an important serine/threonine phosphatase, a highly conserved enzyme widely expressed in eukaryotic cells, which accounts for a majority of the serine/threonine phosphatase activity in cells implicated in regulation of immune signaling pathways and antiviral response. However, most of studies about PP2A have been conducted in mammals but few in crustaceans. In this study, two subunits of PP2A (named as CqPP2Ab and CqPP2Ac ) were characterized to be involved in white spot syndrome virus (WSSV) infection in the haematopoietic tissue (Hpt) cells from red claw crayfish Cherax quadricarinatus . The open reading frame (ORF) of CqPP2Ab was 1341 bp encoding 446 amino acids with seven WD40 domains, and the ORF of CqPP2Ac was 930 bp encoding 309 amino acids with a PP2Ac domain. Tissue distribution analysis showed that the mRNA transcript of CqPP2Ab and CqPP2Ac were both widely expressed in all the tested tissues with the highest expression in hemocyte, followed by high expression in Hpt. The gene expressions of CqPP2Ab and CqPP2Ac were both significantly down-regulated at 6 h post WSSV infection (6 hpi) in Hpt cells. Importantly, the expression of viral immediate early gene IE1 and late viral gene envelope protein VP28 were both significantly increased post WSSV infection after gene silencing of CqPP2Ab or CqPP2Ac in Hpt cells, suggesting that CqPP2Ab and CqPP2Ac could inhibit WSSV infection in Hpt cells, probably by increasing the antimicrobial substances expression in consideration to the significantly reduced expression of anti-lipopolysaccharide factor, crustin, and lysozyme after gene silencing of CqPP2Ab or CqPP2Ac, respectively. These findings provide a new light on the mechanism of WSSV infection and the antiviral response in crustaceans. Highlights: Cq PP2Ab and  Cq PP2Ac inhibit WSSV replication by increasing the expression of antimicrobial substances. Regulation of WSSV infection by  Cq PP2Ab and  Cq PP2Ac provides new strategy against white spot disease. PP2A provides new insignt into crustacean anti-viral immunity.